2017
DOI: 10.1016/j.bbagen.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical coupling of microtubule-dependent motor teams during peroxisome transport in Drosophila S2 cells

Abstract: Background Intracellular transport requires molecular motors that step along cytoskeletal filaments actively dragging cargoes through the crowded cytoplasm. Here, we explore the interplay of the opposed polarity motors kinesin-1 and cytoplasmic dynein during peroxisome transport along microtubules in Drosophila S2 cells. Methods We used single particle tracking with nanometer accuracy and millisecond time resolution to extract quantitative information on the bidirectional motion of organelles. The transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
(116 reference statements)
1
7
0
Order By: Relevance
“…Rod-shaped mitochondria are attractive to explore the performance of motor-teams since their elongated shape determines a broad distribution of motors on the surface. As we mentioned before, the mechanical communication amongst active motors is expected to be different from that observed in small, rounded organelles as peroxisomes [ 8 ] where active motors are spatially confined to a smaller area and thus they are probably closer to each other.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rod-shaped mitochondria are attractive to explore the performance of motor-teams since their elongated shape determines a broad distribution of motors on the surface. As we mentioned before, the mechanical communication amongst active motors is expected to be different from that observed in small, rounded organelles as peroxisomes [ 8 ] where active motors are spatially confined to a smaller area and thus they are probably closer to each other.…”
Section: Introductionmentioning
confidence: 96%
“…The team performance depends on the biophysical properties of the motors (e.g. [ 3–5 ]), the number of motors participating in the team [ 6 , 7 ], and their mechanical coupling when attached to the cargo surface [ 8–10 ] amongst other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple dyneins are connected directly or indirectly in the cell through molecular or physical interactions to form a functional network of dyneins. For example, intracellular vesicles usually contain multiple dyneins (Hendricks et al, 2010;Encalada et al, 2011;Rai et al, 2013Rai et al, , 2016De Rossi et al, 2017;Chowdary et al, 2018;Cella Zanacchi et al, 2019), and the clustering enables a team of dyneins to produce collective large stall forces Rai et al, 2013). A recent super-resolution study also reported that dynein forms nanoclusters composed of up to seven dimers on microtubules (Cella Zanacchi et al, 2019).…”
Section: Network Of Dyneinsmentioning
confidence: 99%
“…Besides activation by adaptor proteins, dynein can also be mechanically activated (Monzon and Scharrel et al, 2019;Torisawa et al, 2014). Ally et al (2009) have shown that a mechanical motor coupling is needed for cargo transport and De Rossi et al (2017) hypothesize that motors might activate each other by exerting forces on the opposite motor team. Mechanical dynein activation has been shown to determine the velocity in unidirectional dynein-driven transport (Monzon and Scharrel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%